2022
DOI: 10.1155/2022/3432235
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Antibacterial and Antibiofilm Activity of Selenium Nanoparticles against Vibrio cholerae as a Potent Therapeutics

Abstract: Vibrio cholerae is a major cause of severe diarrhea, which is ecologically flexible, and remains as a major cause of death, especially in developing countries. Consecutive emergence of antibiotic-resistant strains is considered to be as one of the major concerns of the World Health Organization (WHO). Nanoparticles as a new nonantibiotic therapeutic strategy have been widely used in recent years to treat bacterial infections. The present study aimed to investigate the antibacterial and antibiofilm effect of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The minimum biofilm inhibitory concentration (MBIC) of SeNPs was determined following the protocol of Bagheri-Josheghani et al [ 26 ], with a slight modification of the broth used in the experiment. Aliquots of 10 µL of CRAB isolates (concentration of 10 8 CFU/mL) were incubated overnight at 37 °C in microtiter plates containing 100 µL of doubled-strength MH broth and 100 µL of SeNPs (concentrations ranging from 1.25–0.0015 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The minimum biofilm inhibitory concentration (MBIC) of SeNPs was determined following the protocol of Bagheri-Josheghani et al [ 26 ], with a slight modification of the broth used in the experiment. Aliquots of 10 µL of CRAB isolates (concentration of 10 8 CFU/mL) were incubated overnight at 37 °C in microtiter plates containing 100 µL of doubled-strength MH broth and 100 µL of SeNPs (concentrations ranging from 1.25–0.0015 mg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The antibacterial capabilities of the as-synthesized SeNPs aided the oxidative impairments generated by ROS. The findings revealed that various bacteria might be efficiently suppressed and damaged, implying that biosynthesized SeNPs may be used as antimicrobial agents to treat bacterial pathogenic infections [ 77 ].…”
Section: Role Of Senps In Several Diseasesmentioning
confidence: 99%